2005
DOI: 10.1073/pnas.0508950102
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk in G protein-coupled receptors: Changes at the transmembrane homodimer interface determine activation

Abstract: Functional crosstalk between G protein-coupled receptors in a homo-or heterodimeric assembly likely involves conformational changes at the dimer interface, but the nature of this interface is not yet established, and the dynamic changes have not yet been identified. We have mapped the homodimer interface in the dopamine D2 receptor over the entire length of the fourth transmembrane segment (TM4) by crosslinking of substituted cysteines. Their susceptibilities to crosslinking are differentially altered by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

48
287
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(339 citation statements)
references
References 56 publications
48
287
4
Order By: Relevance
“…11 Combined essential dynamics of these simulations showed that the most pronounced changes within the transmembrane region of the rhodopsin dimer occurred at the dimerization interface. Albeit consonant with the rearrangement of the dimer interface observed for the cognate dopamine D2 receptor, 10 the results of these simulations do not allow discriminating among the different dynamic mechanisms that could account for such a conformational rearrangement. In fact, calculations were limited by the system size and submicrosecond time scales accessible with current computer hardware and algorithms.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…11 Combined essential dynamics of these simulations showed that the most pronounced changes within the transmembrane region of the rhodopsin dimer occurred at the dimerization interface. Albeit consonant with the rearrangement of the dimer interface observed for the cognate dopamine D2 receptor, 10 the results of these simulations do not allow discriminating among the different dynamic mechanisms that could account for such a conformational rearrangement. In fact, calculations were limited by the system size and submicrosecond time scales accessible with current computer hardware and algorithms.…”
Section: Introductionmentioning
confidence: 81%
“…Additional cross-linking data of cysteine mutants at the D2DR homo-dimer interface in the presence of agonists and inverse agonists 10 suggested the occurrence of a conformational rearrangement of the dimer interface upon receptor activation. Specifically, agonists accelerated crosslinking of a set of residues on a different TM4 face than the one preferred by the inverse agonist, while diminished crosslinking was recorded for residues on the interface preferred by the inverse agonist.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional contacts involving the cytosolic ends of H3, H4 and IL2 are shown by the CXCR4 complex with the cyclic peptide [29]. For the D 2 R, cysteine crosslinking experiments interpreted in the context of the structural models highlighted the potential rearrangements of the dimer architecture depending on the receptor functional state, the H4-H5 and H4-H4 contact dimers being, respectively, associated with inactive and active states [25,26]. In a more recent study, the same authors provided evidence that D 2 R forms higher-order oligomers in living cells and that H1 and H8 form a second symmetric interface in addition to the previously identified H4 interface [16].…”
Section: Introductionmentioning
confidence: 99%
“…System's dependent variety in the dimer architecture emerges also from results of in vitro experiments. In this respect, the highest resolution information available thus far comes from X-ray crystallography and atomic force microscopy (AFM) measurements on rhodopsin, opsin, b 2 -AR and CXCR4 chemokine receptor, as well as from cysteine crosslinking experiments on D 2 receptor (D 2 R), and disulphide trapping experiments on 5HT 1c receptor [22][23][24][25][26][27][28][29]. With regard to rhodopsin, the geometrical constraints from AFM measurements led to the proposal of a semi-empirical model of a higher order rhodopsin structure [22].…”
Section: Introductionmentioning
confidence: 99%